Midnight at the Pera Palace : the birth of modern Istanbul - King, Charles, 1967- (W.W. Norton and Company, 2014)
"In this ... portrait of urban reinvention, Charles King re-creates an era when an ancient city became a global crossroads--a forgotten moment when Europe's closest Muslim metropolis became its vital port of refuge"--Provided by publisher.